Marking behavior of Andean bears in an Ecuadorian cloud forest: a pilot study - Filipczykova, E. (2016)
Very little is known about the general ecology and marking behavior in specific of the endangered Andean bear (Tremarctos ornatus). Such knowledge is, however, indispensable for their effective conservation and management. Here, we present a first detailed description of Andean bear marking behavior using camera traps. From November 2012 to April 2013, we inspected 16 bear trails in the Ecuadorian Napo province, and installed camera traps (3) at marking sites to document their marking behavior. We obtained 22 video recordings of Andean bears, all of which were captured during daytime. Scent marking was the main behavioral display, and consisted of (i) tree sniffing, (ii) rubbing the neck and/or shoulders, (iii) the hindquarters, and (iv) the back. We only observed scent marking from males. In compliance with other bear species, we suggest that Andean bears communicate intraspecifically and intrasexually through their marking behavior.